Answer:
(x+3)(x-5)=(x+3)(x-5)
x^2-2 = x^2-2
Step-by-step explanation:
Answer:
f(1) = 24
Step-by-step explanation:
f(1) is the value of f(x) when x = 1, that is from the table
f(1) = 24
<em>So</em><em> </em><em>the</em><em> </em><em>right</em><em> </em><em>answer</em><em> </em><em>is</em><em> </em><em>of</em><em> </em><em>option</em><em> </em><em>C</em><em>.</em>
<em>HOPE</em><em> </em><em>THIS</em><em> </em><em>WILL</em><em> </em><em>HELP</em><em> </em><em>U</em><em>.</em><em>.</em><em>.</em><em>=</em><em>)</em>
Well, I can't figure out the answer at the moment, but I can give you a tip. Just substite each possible sign in the to see if one works... for example: +++, x+-, ++-....
Hope this helps you out :)